Factors influencing the concordance of histological subtype diagnosis from biopsy and resected specimens of lung adenocarcinoma. (April 2016) - Matsuzawa, Reiko; Kirita, Keisuke; Kuwata, Takeshi; Umemura, Shigeki; Matsumoto, Shingo; Fujii, Satoshi; Yoh, Kiyotaka; Kojima, Motohiro; Niho, Seiji; Ohmatsu, Hironobu; Ochiai, Atsushi; Tsuboi, Masahiro; et al.
Highlights: Predominant subtype of adenocarcinoma is associated with genetic abnormalities and clinicopathological features. We investigated the predominant subtypes in biopsy samples focusing on the concordance with the resected samples. The subtypes diagnosed by biopsy samples could be reliable as a predictive marker when the area is large enough. Abstract: Objectives: Lung adenocarcinoma is heterogeneous, characterized by various histological subtypes. Determination of the predominant histological subtype (lepidic, papillary, acinar or solid-predominant) has been shown to correlate with genetic abnormalities and clinicopathological features. Although subtyping using small biopsy samples is important for tailored approaches to clinical management, limited data exist on the concordance of predominant subtype between resected specimens and biopsy specimens. Materials and methods: We compared the diagnosed predominant subtypes in resected specimens and matched biopsy specimens in a series of 327 lung adenocarcinomas. The accuracy of preoperative diagnosis by biopsy and the factors that influence concordance with resected specimen analysis were examined. Results: In 211 of the 326 patients (66.0%), the predominant adenocarcinoma subtype diagnosed from biopsy matched the findings of resection analysis. Overall, the concordance rate in biopsy samples with larger tumor areas (≥0.7 mm 2 ) was significantly higher than in those with smaller tumor area (<0.7 mm 2 ; 71.2% vs 60.7%, respectively; p = 0.015). In the biopsy samples with smaller tumor areas, the concordance rate was 77% in lepidic subtype, 71% in papillary subtype, 60% in solid subtype, and 40% in acinar subtype. Concordance rate in the biopsy samples with larger tumor area was higher in papillary and solid subtypes (88% and 76%, respectively), but remained low in acinar subtype (37%). Conclusion: The current results indicate that accuracy of adenocarcinoma subtyping based on small biopsy samples is influenced by tumor area. Our study also suggests that subtyping of acinar histology using biopsy specimen is particularly error-prone.